Family Support Relationships Degrees of Diabetic Foot Wounds - Mas’ud, Alfian; Najman, Najman; Artifasari, A.; Nilmawati, Nilmawati (Journal La Medihealtico, 2023)
Changes in lifestyle can cause degenerative diseases such as Diabetes Mellitus (DM). The prevalence and incidence of this disease has increased drastically in industrialized and developing countries, including Indonesia. WHO predicts that DM data will increase to 300 million in the next 25 years. The International Diabetes Federation (IDF) estimates that in 2020 there will be 178 million DM sufferers in Indonesia aged over 20 years and assuming a DM prevalence of 4.6%, there will be 8.2 million DM patients. Currently, the prevalence of DM based on the International Diabetes Federation (IDF) in 2019, Indonesia is ranked 6th in the world with 10 million people. Based on the 2007 Riskesdas results, it is estimated that 463 million people suffer from diabetes currently and it is projected to reach 578 million in 2030. and 700 million in 2045. This study was to determine the relationship between family support and the degree of Diabetic Foot Ulcers (DFU). The design of this research is an analytical observational study with a cross-sectional approach design. The subjects of this study were DM sufferers with diabetic foot ulcers who underwent treatment at the Independent Wound Nursing Practice in Bone Regency. The sampling technique uses the Total Sampling method. After carrying out the Pearson correlation test, test results were obtained with a p value = 0.000 and an r value = 0.648** so it can be concluded that there is a very strong correlation between family support and the degree of diabetic foot ulcers. So it can be concluded that the higher the family support for patients with diabetic foot ulcers, the lower the degree of injury. The results of this study can be concluded that there is a strong relationship between family support and the degree of injury in Diabetic Foot Ulcer (DFU) patients so that caring for families with diabetic foot ulcers will provide good encouragement for diabetic foot ulcer patients so they can heal and follow the treatment program. the good one.